A serodiagnostic test for tuberculosis. - Nicholls, A C (1975)
This study describes a simple whole cell agglutination test for tuberculosis in which phenol-killed Mycobacterium tuberculosis H37Ra is used as the antigen. The test gave positive results in 59 of 63 culture-positive cases of tuberculosis due to M. tuberculosis, and in 4 of 11 culture-positive cases due to other mycobacteria. Negative results were recorded in 168 of 171 control subjects. A positive result was one in which a titre of 1/125 or more was recorded.